Policy Reform As Collective Action - Johnson, Omotunde (Washington, D.C. : International Monetary Fund, 1997)
A government desiring support for its policy reform program, without coercion, behaves as if it faces a political constraint. Citizen support depends on the estimate, by at least some minimum proportion of the population, that the program will succeed and the outcome will be in their individual self-interest. Government behavior has implications for the program, whose contents constitute the set of signals used by citizens to estimate the probability that the program will succeed. The government uses various devices to mobilize support for its program. An informed expert could design a program acceptable to both the government and the citizens.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government Welfare Function; Models Of Political Processes; Reform Program; State-Society Type; WP